Astragali radix: could it be an adjuvant for oxaliplatin-induced neuropathy? - Di Cesare Mannelli, Lorenzo (Sci Rep, 2017)
Neurotoxicity is a major side effect of platinum derivatives both during and after treatment. In the absence of effective pharmacological compounds, the opportunity to identify safe adjuvant treatments among medicinal plants seems appropriate. Astragali radix is an adaptogenic herbal product recently analyzed in platinum-treated cancer patients. With the aim of evaluating the anti-neuropathic profile of Astragali radix, a previously characterized aqueous (Aqu) and two hydroalcoholic (20%HA and 50%HA) extracts were tested in a rat model of oxaliplatin-induced neuropathy. Repeated administrations significantly reduced oxaliplatin-dependent hypersensitivity with 50%HA, the most effective, fully preventing mechanical and thermal hypersensitivity. Ex vivo, 50%HA reduced morphometric and molecular alterations induced by oxaliplatin in peripheral nerve and dorsal-root-ganglia. In the spinal cord and in brain areas, 50%HA significantly decreased activation of microglia and astrocytes. Furthermore, 50%HA prevented the nephro- and hepato-toxicity induced by the anticancer drug. The protective effect of 50%HA did not alter oxaliplatin-induced apoptosis in colon tumors of Pirc rats, an Apc-driven model of colon carcinogenesis. The hydroalcoholic extract (50%HA) of Astragali radix relieves pain and promotes the rescue mechanisms that protect nervous tissue from the damages triggering chronic pain. A safe profile strongly suggests the usefulness of this natural product in oxaliplatin-induced neuropathy.